How do parents perceive adverse drug events of their children's anticonvulsant medication?. (May 2018) - Bach, V.A.; Neininger, M.P.; Spindler, U.P.; Hotopp, L.C.; Hornemann, F.; Syrbe, S.; Merkenschlager, A.; Kiess, W.; Bernhard, M.K.; Bertsche, T.; Bertsche, A.
Abstract: Background: The main source of knowledge on adverse drug events (ADE) are physicians' reports in controlled clinical trials. In contrast, little is known about the parents' perception of ADE of anticonvulsants their children receive. Methods: After approval by the local ethics committee, we performed a survey in a neuropediatric outpatient clinic of a university hospital. Based on a structured questionnaire, we interviewed parents of children with current anticonvulsant treatment regarding (i) their fears about potential ADE, (ii) experienced ADE according to parents, and (iii) implications of ADE on the child's life. Results: Parents of 150 patients took part in the interview. (i) 95 (63.3%) parents expressed fears concerning ADE, mostly liver injury/liver failure (33 [22%]). (ii) 129 (86%) parents reported experienced ADE, mostly sedation (65 [43.3%]) and abnormal behavior (54 [36%]). (iii) Parents reported substantial implications of ADE on the child's daily life for 84 (56%) children, and 63 (42%) parents expressed a negative impact on the child's development. Conclusion: We recognized a great discrepancy between those ADE that were feared and those that were experienced. Parents feared life-threatening ADE and experienced less severe ADE that nevertheless have a negative impact on the child's daily life. Highlights: 63% parents feared adverse drug events of their children's anticonvulsants. Adverse drug events mostly feared concern liver and kidney function. 86% parents reported experienced adverse drug events caused by anticonvulsants. Adverse drug events mostly experienced were sedation and abnormal behavior. 56% reported substantial implications of adverse drug events on the child's life.